A representatividade feminina em uma multinacional localizada do município de Juruti - PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
When considering the goal of the United Nations (UN), which aims for gender equality by the year 2030, and also the great challenge of women's participation in the mining sector, it is necessary to monitor the advances and spaces that women have been occupying in companies that operate in mining. This study analyzed the behavior of the growth of female representation in a multinational company located in the municipality of Juruti, in order to quantify the growth of female employees, and also how the women who work in the local mining company feel about issues of inclusion and gender equity. The research was carried out by applying a questionnaire via an electronic and physical form, as well as in a bibliographical way, in order to compare scenarios between two other large mining companies. With this study, the opinion of some female employees was obtained, regarding the barriers faced by women in mining, and whether they have ever suffered harassment in their work environment, among other information related to their professional careers. The percentage of female employees working at the mining company, was disclosed by the company, a number of approximately 25% of women in the mining company and about 7% in its contracted companies for the provision of various services. Finally, through the research carried out, it was possible to verify the growth of the female workforce at the company in question and the goals of the company and the mining sector for gender equality by 2030.
Keywords: Mulher na mineração; Mineração; Juruti; Inclusão de gênero; CNPQ:: CIÊNCIAS EXATAS